Summary Prosedures and Optimization of Commercial Court Proceedings in Russia - S. Nikitin; M. Patsatsiya (BRICS Law Journal, 2019)
This article deals with the problems involved in implementing simplified forms of legal proceedings in the Russian civil process, which is one of the important directions for optimizing commercial court proceedings. The study is largely based on the analysis of previously unpublished statistical information on the commercial courts of three districts for the period of 2016–2018, showing the results of their procedural activities in the framework of the procedures of simplified and writ proceedings in the context of court data of the commercial court system as a whole. The obtained results are highlighted taking into account domestic, foreign and international experience, doctrinal approaches and the existing need for the optimization of commercial court proceedings. The authors substantiate the conclusion that the consideration of cases in the procedures of simplified production facilitates significantly reducing the caseload burden on the commercial courts of first instance, both by simplifying the procedures for the consideration of these cases and by drawing up judicial acts on them. The article formulates proposals for the development of the current commercial procedural law, in particular the proposal to unify the procedural order of commercial court cases on the recovery of compulsory payments and sanctions. It further proposes possible variants of such unification.